Nicorandil Ameliorates Depression‐Like Behaviors After Traumatic Brain Injury by Suppressing Ferroptosis Through the SLC7A11/GPX4 Axis in the Hippocampus - Yao‐Ran Tu; Ming Tan; Yao Li; De‐Quan Hong; Fan Niu (Brain and Behavior)
ABSTRACT Introduction Depression is a prevalent and significant psychological consequence of traumatic brain injury (TBI). Ferroptosis, an iron‐dependent form of regulated cell death, exacerbates the neurological damage associated with TBI. This study investigates whether nicorandil, a potassium channel opener with nitrate‐like properties known for its antioxidative and neuroprotective effects, can mitigate depression‐like behaviors following TBI by modulating ferroptosis. Methods A controlled cortical impact (CCI) device was used to establish the TBI model. Depression‐like behaviors in rats were assessed using the sucrose preference test (SPT), the tail suspension test (TST), and the forced swimming test (FST). The antioxidant system, lipid peroxidation, and ferroptosis levels were evaluated. The SLC7A11/GPX4 axis was analyzed using quantitative real‐time PCR (qRT‐PCR) and Western blot analysis. Results Nicorandil administration significantly ameliorated depression‐like behaviors in rats with TBI. Nicorandil administration also effectively restored the antioxidant system, substantially reduced lipid peroxidation, and attenuated ferroptosis in the hippocampus of rats with TBI. Mechanistically, nicorandil administration promoted the SLC7A11/GPX4 axis in the hippocampus of rats with TBI. Crucially, knockdown of hippocampal SLC7A11 abrogated the protective effects of nicorandil on depression‐like behaviors, lipid peroxidation, and ferroptosis in the hippocampus of rats with TBI. Conclusion These findings indicate that nicorandil ameliorates depression‐like behaviors following TBI by inhibiting hippocampal ferroptosis through the activation of the SLC7A11/GPX4 axis.